The impact of social networks sites on interpersonal communication - زريقة يسرى; قصير هلا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
" Social Networks sites " and "Interpersonal Communication " are new interesting concepts, which no one in our time can do without. Because of the imbalances and changes that have occurred recently in the level of social relations and personal communication between individuals, due to the large number of unorganized use of social networking sites, we found the need to research the reality of this phenomenon that led to the emergence of a problem in the distance of individuals from personal contact between them, and replace it with contact Electronic by resorting to a virtual world that lacks social interaction and face-to-face communication.Based on this, this study seeks to identify the concept of social networking sites, their types, forms and features, and to address the reasons that drive individuals to use them, and to identify the concept of personal communication by providing some definitions, functions and characteristics that distinguish it, and highlight its importance in light of the use of social networking sites. The study uses the descriptive approach in order to reach some conclusions, recommendations and proposals to alleviate the phenomenon of using social networking sites.